Investigation of Thermodynamic Properties of Metal Thin Film by Statistical Moment Method - Hung, Vu Van; Phuong, Duong Dai; Hoa, Nguyen Thi (Communications in Physics, 2013)
The thermodynamic properties of the metal thin film with face-centered cubic structure at zero pressure are investigated using the statistical moment method \((SMM)\), including the anharmonicity effects of thermal lattice vibrations. The Helmholtz free energy, linear thermal expansion coefficients, specific heats at the constant volume and those at the constant pressure, \(C_V\) and \(C_p\) are derived in closed analytic forms in terms of the power moments of the atomic displacements. Numerical calculations for thermodynamic quantities of Al, Au and Ag thin films are found to be in good agreement with those of the other theoretical results and experimental data.